Muscle Mass to Visceral Fat Ratio Is an Important Predictor of the Metabolic Syndrome in College Students - Garcia-Hermoso, A (Cambridge University Press, 2019)
This study aimed to evaluate the associations between the muscle mass to visceral fat (MVF) ratio and cardiometabolic risk factors in a large population of college students in Colombia and to propose cut-off points of this index for the metabolic syndrome (MetS). A total of 1464 young adults recruited from the FUPRECOL (Asociación de la Fuerza Prensil con Manifestaciones Tempranas de Riesgo Cardiovascular en Jóvenes y Adultos Colombianos) study were categorised into four groups based on their MVF ratio. Muscle mass and visceral fat level of the participants were measured using a bioelectrical impedance analysis. Cardiometabolic risk factors including lifestyle characteristics, anthropometry, blood pressure and biochemical parameters were assessed. The prevalence of moderate to severe obesity, hypertension and the MetS was higher in subjects in quartile (Q)1 (lower MVF ratio) (P <0·001). ANCOVA revealed that the subjects in Q1 had higher cardiometabolic disturbances, including altered anthropometry, blood pressure, muscle strength and biochemical parameters after adjusting for age and sex compared with young adults in higher MVF ratio quartiles (P <0·001). Muscular mass and physical activity levels were significantly lower in subjects with a lower MVF ratio (P <0·001). The receiver operating characteristic curve analyses indicated that in men the best MVF ratio cut-off point for detecting the MetS was 18·0 (AUC 0·83, sensitivity 78 % and specificity 77 %) and for women, the MVF ratio cut-off point was 13·7 (AUC 0·85, sensitivity 76 % and specificity 87 %). A lower MVF ratio is associated with a higher risk cardiometabolic profile in early adulthood, supporting that the MVF ratio could be used as a complementary screening tool that may help clinicians identify young adults at high cardiometabolic risk. © The Authors 2018.